2018
DOI: 10.1002/hed.25434
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicity in locally advanced head and neck cancer patients treated with induction chemotherapy followed by intermediate or high‐dose cisplatin‐based chemoradiotherapy

Abstract: Background This study evaluated ototoxicity in locally advanced head and neck cancer patients treated in the CONDOR study with docetaxel/cisplatin/5‐fluorouracil (TPF) followed by conventional radiotherapy with concomitant cisplatin 100 mg/m2 on days 1, 22, and 43 (cis100+RT) versus accelerated radiotherapy with concomitant cisplatin weekly 40 mg/m2 (cis40+ART). Methods Sixty‐two patients were treated in this study. Audiometry was performed at baseline, during TPF, before start of chemoradiotherapy, and 1, 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Our findings on cumulative cisplatin dosage effects concur with literature [ 9 , 42 , 45 , 46 ] which reports higher cumulative doses to have a greater impact on hearing thresholds, with more patients in the high-dose group than the low-dose group reflecting a Grade 2/3 category of the NCI-CTCAE grading scale at the six-month post treatment follow-up. While Whitehorn et al [ 35 ] reported that median cumulative dosages of 180.70 mg/m 2 and 236.84 mg/m 2 were likely to result in ototoxic hearing loss for the ototoxicity-free and ototoxicity groups, respectively, our study revealed that increasing cumulative dosages from 150mg/m 2 have increasing effects in the high and extended high-frequency region bilaterally, with a plateau effect seen in the left ear at 250mg/m 2 , with no further change in hearing thresholds at increased dosages.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings on cumulative cisplatin dosage effects concur with literature [ 9 , 42 , 45 , 46 ] which reports higher cumulative doses to have a greater impact on hearing thresholds, with more patients in the high-dose group than the low-dose group reflecting a Grade 2/3 category of the NCI-CTCAE grading scale at the six-month post treatment follow-up. While Whitehorn et al [ 35 ] reported that median cumulative dosages of 180.70 mg/m 2 and 236.84 mg/m 2 were likely to result in ototoxic hearing loss for the ototoxicity-free and ototoxicity groups, respectively, our study revealed that increasing cumulative dosages from 150mg/m 2 have increasing effects in the high and extended high-frequency region bilaterally, with a plateau effect seen in the left ear at 250mg/m 2 , with no further change in hearing thresholds at increased dosages.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the TREMPLIN randomized phase II study, in which ICT followed by CRT using high-dose CDDP was compared with ICT followed by cetuximab plus radiotherapy for larynx preservation, revealed that residual renal dysfunction (grade 1) and grade 3-4 neuropathy were observed in 22.4 and 3.4% of cases after CRT, respectively (17). Late toxicities induced by high-dose CDDP included nephrotoxicity, neurotoxicity, and ototoxicity (17)(18)(19)(20), which are irreversible and likely to reduce quality of life in patients treated with CRT. CDDP-induced nephrotoxicity is dose-dependent and involves necrosis, apoptosis, and necroptosis of renal cells (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…One significance of this trial is the prospective follow-up for late toxicities, focusing on swallowing function, hearing function, and thyroid functions. Of these, ototoxicity is caused by cochlear toxicity due to CDDP and irradiation, and is irreversible, and is likely to reduce the QOL in patients treated with CRT [ 6 ]. Although the American Speech-Language-Hearing Association and the American Academy of Audiology recommend audiological assessments before, during, and after ototoxic drug administration [ 26 , 27 ], monitoring for ototoxicity in clinical practice remains underutilized in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%